PERANCANGAN PLTS ATAP DI GEDUNG KANTOR BUPATI JEMBRANA - Yusuf Firmansyah, Ahmad; Dwi Giriantari, Ida Ayu; Sukerayasa, I Wayan (Jurnal SPEKTRUM, 2023)
According to the Ministry of Energy and Mineral Resources, in the year 2020, Indonesia possessed an electricity generation capacity of 70.96 Gigawatts. Out of this capacity, 35.36% was derived from coal, 19.36% from natural gas, 34.38% from oil, and only 14.96% from Renewable Energy sources. In order to accelerate the adoption of Renewable Energy, in accordance with the Governor of Bali Regulation No. 5 of 2022, there was an encouragement to utilize rooftop Solar Power Generation (PLTS) amounting to at least 20% of the installed electricity capacity or the roof area of both new and existing Government buildings, whether at the Central or Regional levels. Therefore, a rooftop PLTS design for the Jembrana Regency Office Building was essential to support the transition to cleaner energy. The rooftop PLTS design was carried out using the Helioscope software. The rooftop PLTS design for the Jembrana Regency Office Building showed that for the scenario involving the entire roof area, it could generate 174.15 MWh in one year, which translates to 42.51% of the total electricity demand. Meanwhile, for the scenario involving only the North-facing roof, the rooftop PLTS could produce 96.55 MWh in one year, equivalent to supplying 23.57% of the total electricity demand.